On Searle and the collapse of civilization - González-Fernández, Rodrigo (Cinta de Moebio. Revista de Epistemología de Ciencias Sociales, 2020)
This article addresses a neglected problem in Searle’s social ontology, namely, how human civilization may collapse. In the first section, I provide the theoretical framework. In the second section, I offer the key elements to understanding Searle’s ontology as well as his philosophy of society, emphasizing the role of constitutive rules and deontic powers. In the third section I examine how they improve trust and co-operation. Global and local natural disasters are distinguished in the fourth section, because the former is sufficient to undermine pacts, promises, constitutive rules and deontic powers, while the latter is neither sufficient nor necessary. In the fifth and final section, I put forward an argument via a thought experiment that allows us to anticipate what would occur if people did not keep promises and pacts, on the one hand, and did not respect constitutive rules and deontic powers, on the other hand. Such events, I argue, would result in the collapse of civilization.